SOCIETIES EXPECTATION AND LIBRARY VALUES: CONTENT ANALYSIS OF THE MOVIE “SMART LIBRARY MAKES SMART PEOPLE" - Kamaludin, Kamaludin (Journal of Documentation and Information Science, 2018)
Library services are now becoming very important as mandated by law no. 43 the year 2007, in article 14 (1) that library services are primed and oriented to the interests of the user. From that article, the role of librarians is essential in improving services. This study aims to determine the content of the messages available on a movie with title ?Smart library makes smart people? especially the signal related to societies? expectation to the library and the value that can be given by librarian to the users. The method used in this research is using content analysis. The research subject is a documentary movie produced by UPT Balai Informasi Teknologi-LIPI, Bandung, Indonesia, in 2015. The results showed that societies? expectations could be seen at minute 11:18 of the movie that librarian cannot just expect societies to come to the library, but the library has to come to visit them. One of the vital source of strength, the formation of a nation the role-played by print culture. By reading might get some ideas and how to fulfill the plans. Because reading is a kind of bridge to the future. Other users expect at minute 15:46 that there is new technology, the library must move from old-fashioned to the electronic library. The original problem is about big data, but big data is critical to the future. The value that can be given to the users can be seen at minute 09:45 library has assisted to the provinces in Indonesia more than 600 mobile libraries. For the outer island, there are seven free libraries. In Jakarta, there is a Pusteling, a library and an electronic mobile completed with the laptop and internet. At minute 05:40 it is essential to be a growing library, the librarian must have innovation, creativity, and love of work, if there is no innovation from the librarian, there will be no innovation, no new services, and the library will be stagnant, traditional, no improvement.